Gastrointestinal Dysmotility in Rett Syndrome - Baikie, G.; Ravikumara, M.; Downs, J.; Naseem, N.; Wong, K.; Percy, A.; Lane, J.; Weiss, B.; Ellaway, C.; Bathgate, Katherine; Leonard, H. (Lippincott Williams & Wilkins, 2013)
Objectives: Through evidence review and the consensus of an expert panel, we developed recommendations for the clinical management of gastroesophageal reflux disease, constipation, and abdominal bloating in Rett syndrome.Methods: Based on review of the literature and family concerns expressed on RettNet, initial draft recommendations were created. Wherein the literature was lacking, 25 open-ended questions were included. Input from an international, multidisciplinary panel of clinicians was sought using a 2-stage modified Delphi process to reach consensus agreement. Items related to the clinical assessment and management of gas troesophageal reflux disease, constipation, and abdominal bloating.Results: Consensus was achieved on 78 of 85 statements. A comprehensive approach to the assessment of gastroesophageal reflux and reflux disease, constipation, and abdominal bloating was recommended, taking into account impairment of communication skills in Rett syndrome. A stepwise approach to the management was identified with initial use of conservative strategies, escalating to pharmacological measures and surgery, if necessary.Conclusions: Gastrointestinal dysmotility occurs commonly in Rett syndrome. These evidence- and consensus-based recommendations have the potential to improve care of dysmotility issues in a rare condition and stimulate research to improve the present limited evidence base.